Method for preparing potassium sulfate fertilizer and nano-hydroxyapatite from ardealite
Through the metathesis reaction of phosphogypsum and potassium chloride, potassium sulfate fertilizer and nano-hydroxyapatite are prepared, which solves the problem of difficulty in recycling by-product calcium chloride, and realizes resource utilization and heavy metal adsorption, reduces the risk of environmental pollution, and is in line with the concept of green chemistry and circular economy.
Patent Information
- Application Number
- CN202411958784.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-30
- Publication Date
- 2025-04-08
AI Technical Summary
When the prior art uses phosphogypsum to produce potassium sulfate, the by-product calcium chloride is difficult to recover, which poses a risk of environmental pollution, and limits industrial applications.
Potassium sulfate fertilizer is prepared by metathesis reaction between phosphogypsum and industrial potassium chloride, and nano-hydroxyapatite is prepared by using the by-product calcium chloride to adsorb heavy metals in the water to achieve the purpose of "treat waste with waste".
The resource utilization of phosphogypsum was realized, high value-added potassium sulfate products were prepared, and heavy metals were effectively adsorbed through nano-hydroxyapatite, reducing the risk of environmental pollution and in line with the development concept of green chemistry and circular economy.
Smart Images

Figure CN119774568A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of industrial solid waste resource utilization and wastewater treatment, and in particular to a method for preparing potassium sulfate fertilizer and nano-hydroxyapatite by utilizing phosphogypsum. Background Art
[0002] Phosphogypsum is a general industrial solid waste generated during the wet process of phosphoric acid production, and its main component is CaSO4·2H2O.
[0003] Potassium sulfate, as an important chlorine-free potassium fertilizer, plays an irreplaceable role in agricultural production. Although there are two main methods for producing potassium sulfate from phosphogypsum, namely the one-step method and the two-step method, the one-step method faces some challenges in practical application. The one-step method usually uses ammonia as a catalyst to produce potassium sulfate through the direct reaction of phosphogypsum and potassium chloride. This method is relatively simple in process and can directly generate the target product. However, its main problem is the difficulty in recovering the by-product calcium chloride and the potential risk of environmental pollution. Since calcium chloride is produced in large quantities during the reaction process, if it cannot be effectively recovered and utilized, it will have an adverse impact on the environment, which also limits the industrial application of the one-step method.
[0004] Heavy metal pollution has the characteristics of high biological toxicity, persistence, and difficulty in degradation. It can be enriched in animals and plants through the food chain, causing its toxicity to be multiplied and seriously affecting aquatic ecology.
[0005] Nano-hydroxyapatite often reacts with heavy metal ions by chemical bonds or electrostatic interactions, and has a strong adsorption capacity for heavy metal ions, while not introducing too many other impurity ions and causing no secondary pollution to the environment. Hydroxyapatite (HPA) is an environmentally friendly biomaterial, and its composition is similar to the chemical composition of human bone and hard tissue, and is non-toxic and has no side effects on the human body.
[0006] Therefore, if phosphogypsum can be used to prepare potassium sulfate and co-produce nano-hydroxyapatite, it will be of great significance to the resource utilization of phosphogypsum. Summary of the invention
[0007] In view of this, the present invention aims to provide a method for preparing potassium sulfate fertilizer and nano-hydroxyapatite using phosphogypsum, wherein phosphogypsum and industrial potassium chloride are used to prepare potassium sulfate fertilizer through double decomposition reaction, and its by-product calcium chloride is used to prepare nano-hydroxyapatite to adsorb heavy metals in water, thereby achieving the purpose of "treating waste with waste" and expanding the utilization of phosphogypsum.
[0008] To achieve the above object, the technical solution of the present invention is achieved as follows:
[0009] A method for preparing potassium sulfate fertilizer and nano-hydroxyapatite by using phosphogypsum comprises the following steps:
[0010] 1) dissolving phosphogypsum and potassium chloride in an ammonia-ethanol mixed solution to obtain slurry A;
[0011] 2) centrifuging the slurry A to obtain a filtrate B and a filter residue;
[0012] 3) evaporating and crystallizing the filtrate B to obtain calcium chloride;
[0013] 4) washing the filter residue with water and then centrifuging to obtain filtrate C;
[0014] 5) evaporating and crystallizing the filtrate C to obtain potassium sulfate;
[0015] 6) After the calcium chloride is dissolved in water, phosphoric acid is added to adjust the solution pH to ≥ 10.5, and then, after stirring and reacting for a period of time, washing, centrifugal separation, and vacuum drying are performed to obtain nano-hydroxyapatite.
[0016] Optionally, in step 1), the mass ratio of the phosphogypsum to the potassium chloride is 1:1.
[0017] Optionally, in step 1), the mass ratio of the total mass of the phosphogypsum and the potassium chloride to the ammonia-ethanol mixed solution is 1:10-1:12.
[0018] Optionally, the crystallization temperature of the evaporative crystallization in step 3) is 200° C., and the crystallization time is not less than 24 hours.
[0019] Optionally, the crystallization temperature of the evaporative crystallization in step 5) is 200° C., and the crystallization time is not less than 18 hours.
[0020] Optionally, the pH of the solution in step 6) is 10.5-11.0.
[0021] Optionally, the stirring rate of the stirring reaction in step 6) is ≥500 rpm, and the stirring time is ≥6 h.
[0022] Optionally, the vacuum drying in step 6) is carried out at a drying temperature of 70° C.-80° C. and for a drying time of 48 h.
[0023] Compared with the prior art, the method for preparing potassium sulfate fertilizer and nano-hydroxyapatite by using phosphogypsum of the present invention has the following advantages:
[0024] 1. The nano-hydroxyapatite prepared by the present invention has an effect on Pb in water 2+ The maximum adsorption capacity is 1400mg / g, Cu 2+ The maximum adsorption capacity is 450 mg / g, Zn 2+The maximum adsorption capacity is 538mg / g, Cd 2+ The maximum adsorption capacity is 900 mg / g. This is because compared with the nano-hydroxyapatite prepared by the conventional method, the nano-hydroxyapatite prepared by the present invention contains hydroxyl particles with reduced size, which is beneficial to the adsorption of heavy metal ions. On the other hand, from the perspective of dissolution and precipitation mechanism, after the particles are reduced in size, the dissolution rate will be accelerated, which is beneficial to shorten the equilibrium time and speed up the removal progress.
[0025] 2. The present invention, through the innovative "one-step" process, not only successfully realizes the resource utilization of phosphogypsum, an industrial by-product, and converts it into a high-value-added potassium sulfate product, but also proposes an efficient and environmentally friendly solution to the problem of waste liquid inevitably generated in the process, that is, using the waste liquid generated in the preparation process to prepare nano-hydroxyapatite. The proposal of this solution has opened up a new way to solve the waste disposal problem that has long plagued the chemical industry.
[0026] 3. The waste liquid treatment path explored by the present invention aims to effectively separate and transform the harmful substances in the waste liquid through a series of carefully designed chemical reactions and separation technologies, such as chemical precipitation, so that it meets the national emission standards or further recycling standards. In this process, not only the risk of environmental pollution is reduced, but also the maximum utilization of resources is achieved, which is in line with the current development concept of green chemistry and circular economy. At the same time, the preparation method of the present invention is simple, low-cost, can turn waste into treasure, is environmentally friendly, and can achieve batch green production. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] The accompanying drawings constituting a part of the present invention are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the accompanying drawings:
[0028] Figure 1 This is a specific implementation process diagram of the preparation of nano-hydroxyapatite according to the present invention;
[0029] Figure 2 This is a STEM image of the nano-hydroxyapatite prepared in Example 1 of the present invention (magnification 120*1000);
[0030] Figure 3 This is a mapping image of the nano-hydroxyapatite prepared in Example 1 of the present invention;
[0031] Figure 4 This is the full spectrum of Ca, P, and O of the XPS of the nano-hydroxyapatite prepared in Example 1 of the present invention;
[0032] Figure 5 The nano-hydroxyapatite prepared in Example 1 of the present invention adsorbs Cu in water 2+Post-mapping image;
[0033] Figure 6 Nano-hydroxyapatite prepared in Example 1 of the present invention adsorbs Pb in water 2+ Post-mapping image;
[0034] Figure 7 The nano-hydroxyapatite prepared in Example 1 of the present invention adsorbs Cd in water 2+ Post-mapping image;
[0035] Figure 8 The nano-hydroxyapatite prepared in Example 1 of the present invention adsorbs Zn in water 2+ Post-mapping image;
[0036] Fig. 9 The XRD diagram of the nano-hydroxyapatite prepared in Example 1 of the present invention is compared with its standard card;
[0037] Fig.10 The removal rate curve of the nano-hydroxyapatite prepared in Example 1 of the present invention when adsorbing heavy metals in water under different dosage conditions;
[0038] Fig.11 This is a curve diagram showing the removal rate of heavy metals in water adsorbed by the nano-hydroxyapatite prepared in Example 1 of the present invention under different pH conditions;
[0039] Fig.12 This is a diagram showing the removal rate of heavy metals in water when adsorbed by the nano-hydroxyapatite prepared in Example 1 of the present invention at different adsorption times. DETAILED DESCRIPTION
[0040] In order to enable those skilled in the art to better understand the technical solutions and technical effects of the present invention, several embodiments are provided below. Obviously, what is described below is only an embodiment and does not limit the protection scope of the present invention.
[0041] Example 1
[0042] like Figure 1 As shown, the method for preparing potassium sulfate fertilizer and nano-hydroxyapatite using phosphogypsum in this embodiment comprises the following steps:
[0043] 1) dissolving phosphogypsum and potassium chloride in an ammonia-ethanol mixed solution at a solid-liquid ratio of 1:10 for 6 hours, wherein the mass ratio of phosphogypsum to potassium chloride is 1:1, to obtain slurry A;
[0044] 2) centrifugally filtering the slurry A to obtain a filtrate B and a filter residue;
[0045] 3) placing the filtrate B from step 2) on a heating plate at 200° C. for evaporation and crystallization for 24 hours to obtain calcium chloride;
[0046] 4) washing the filter residue from step 2) three times with water and centrifuging to obtain filtrate C;
[0047] 5) placing the filtrate C from step 4) on a heating plate at 200° C. for evaporation and crystallization for 18 hours to obtain potassium sulfate;
[0048] 6) After the calcium chloride in step 3) is dissolved in deionized water, phosphoric acid is added dropwise using an acid burette, and the pH is adjusted to 10.5 with aqueous ammonia during the addition. After the phosphoric acid is added dropwise, the magnetic stirrer is maintained at 500 rpm for 6 hours, the generated white precipitate is centrifuged, and the white precipitate obtained by centrifugation is washed three times with water and placed in a vacuum drying oven at 80° C. for vacuum drying for 48 hours to obtain nano hydroxyapatite.
[0049] Comparative Example 1
[0050] The difference between this comparative example and Example 1 is that the solid-liquid ratio in step 1) is 1:5, that is, the mass ratio of the total mass of phosphogypsum and potassium chloride to the ammonia-ethanol mixed solution in step 1) is 1:5. Under this condition, it is found that phosphogypsum and potassium chloride cannot be dissolved at all and subsequent operations cannot be continued.
[0051] Comparative Example 2
[0052] The difference between this comparative example and Example 1 is that the solid-liquid ratio in step 1) is 1:8, that is, the mass ratio of the total mass of phosphogypsum and potassium chloride to the ammonia-ethanol mixed solution in step 1) is 1:8. Under this condition, it is found that phosphogypsum and potassium chloride cannot be dissolved at all and subsequent operations cannot be continued.
[0053] Comparative Example 3
[0054] The difference between this comparative example and Example 1 is that in step 6), the white precipitate obtained by centrifugal separation is washed three times with water and then placed in a microwave oven for drying for 10 minutes.
[0055] The heavy metal adsorption capacity of the materials obtained in Example 1 of the present invention and Comparative Example 3 was tested, and the test results are shown in Tables 1 to 4.
[0056] It can be seen from Tables 1 to 4 that compared with Example 1, the material obtained in Comparative Example 3 adsorbs heavy metals such as Cu 2+ (200mg / L), Pb 2+ 、Zn 2+ 、Cd 2+ The effect was significantly reduced.
[0057] Table 1 Materials in Cu under different drying methods2+ Comparison results at a concentration of 200 mg / l
[0058]
[0059] Table 2 Materials in Pb under different drying methods 2+ Comparison results at a concentration of 100 mg / l
[0060]
[0061] Table 3 Materials in Zn under different drying methods 2+ Comparison results at a concentration of 200 mg / l
[0062]
[0063] Table 4 Cd content of materials under different drying methods 2+ Comparison results at a concentration of 55 mg / l
[0064]
[0065] The nano-hydroxyapatite prepared in Example 1 of the present invention was subjected to HAADF-STEM test, and the test results are as follows: Figure 2 As shown, the magnification is 50nm. Figure 2 It can be seen that the nano-hydroxyapatite formed in Example 1 of the present invention is a typical rod-like structure, and the surface is rough with abundant adsorption sites.
[0066] The nano-hydroxyapatite prepared in Example 1 of the present invention was subjected to mapping and XPS analysis, and the test results are as follows: Figure 3 and Figure 4 As shown. Figure 3 and Figure 4 It can be seen that the nano-hydroxyapatite formed in Example 1 of the present invention contains Ca, P, and O atoms.
[0067] The nano-hydroxyapatite prepared in Example 1 of the present invention adsorbs Cu in water 2+ The mapping analysis is performed on the effect after the test. The test results are as follows Figure 5 As shown. Figure 5 and Figure 3 By comparison, Cu 2+ It is adsorbed into the nano-hydroxyapatite prepared in Example 1 of the present invention.
[0068] The nano-hydroxyapatite prepared in Example 1 of the present invention adsorbs Pb in water 2+ The mapping analysis is performed on the effect after the test. The test results are as follows Figure 6 As shown. Figure 6 and Figure 3 By comparison, Pb2+ It is adsorbed into the nano-hydroxyapatite prepared in Example 1 of the present invention.
[0069] The nano-hydroxyapatite prepared in Example 1 of the present invention adsorbs Cd in water 2+ The mapping analysis is performed on the effect after the test. The test results are as follows Figure 7 As shown. Figure 7 and Figure 3 By comparison, Cd 2+ It is adsorbed into the nano-hydroxyapatite prepared in Example 1 of the present invention.
[0070] The nano-hydroxyapatite prepared in Example 1 of the present invention adsorbs Zn in water 2+ The mapping analysis is performed on the effect after the test. The test results are as follows Figure 8 As shown. Figure 8 and Figure 3 By comparison, Zn 2+ It is adsorbed into the nano-hydroxyapatite prepared in Example 1 of the present invention.
[0071] The nano-hydroxyapatite prepared in Example 1 of the present invention was subjected to XRD test and the result was compared with the standard card of hydroxyapatite. Fig. 9 As shown. Fig. 9 It can be seen that the peak shape is sharp and clear, and other impurities have no obvious diffraction peaks, indicating that relatively pure nano-hydroxyapatite can be prepared through the process proposed by the present invention. The position of the characteristic diffraction peak is compared with the standard card of the hydroxyapatite diffraction pattern. The diffraction peaks near 2θ=25.9°, 28.2°, 28.9°, 31.8°, 34.1°, 39.8°, 46.7°, 48.1°, 49.5° and 53.3° correspond to the (002), (102), (210), (211), (202), (310), (222), (312), (213) and (004) crystal planes of hydroxyapatite. It shows that the material successfully prepared by the present invention has several obvious and narrow peaks of hydroxyapatite, indicating that the crystallinity is good.
[0072] The nano-hydroxyapatite prepared in Example 1 of the present invention adsorbs Pb in water under different dosage conditions. 2+ The removal rate effect was tested. 2+ is 200mg / l, the test results are as follows Fig.10 .Depend on Fig.10 It can be seen that under different dosage conditions, the nano-hydroxyapatite prepared in Example 1 of the present invention has an effective amount of Pb 2+ It has good adsorption effect. At 0.5g / l, its adsorption rate can reach 99.89%.
[0073] The nano-hydroxyapatite prepared in Example 1 of the present invention adsorbs Zn in water under different dosage conditions. 2+ The removal rate was tested. Zn in water before adsorption 2+ is 150mg / l, the test results are as follows Fig.10 .Depend on Fig.10 It can be seen that under different dosage conditions, the nano-hydroxyapatite prepared in Example 1 of the present invention has an effect on Zn 2+ It has good adsorption effect. At 5g / l, its adsorption rate can reach 93.56%.
[0074] The nano-hydroxyapatite prepared in Example 1 of the present invention adsorbs Cd in water under different dosage conditions 2+ The effect was tested. Cd in water before adsorption 2+ is 100mg / l, the test results are as follows Fig.10 .Depend on Fig.10 It can be seen that under different dosage conditions, the nano-hydroxyapatite prepared in Example 1 of the present invention has an effective amount of Cd 2+ It has good adsorption effect. At 1.6g / l, the adsorption rate can reach 98.12%.
[0075] The nano-hydroxyapatite prepared in Example 1 of the present invention adsorbs Cu in water under different dosage conditions. 2+ The removal rate of Cu in water before adsorption was tested. 2+ is 200mg / l, the test results are as follows Fig.10 .Depend on Fig.10 It can be seen that under different dosage conditions, the nano-hydroxyapatite prepared in Example 1 of the present invention has an effect on Cu 2+ It has good adsorption effect. At 5g / l, its adsorption rate can reach 99.53%.
[0076] The nano-hydroxyapatite prepared in Example 1 of the present invention adsorbs Pb in water under different pH conditions. 2+ The removal rate effect was tested. The Pb in the water before adsorption 2+ is 200mg / l, the test results are as follows Fig.11 .Depend on Fig.11 It can be seen that under different pH conditions, the nano-hydroxyapatite prepared in Example 1 of the present invention has a significant effect on Pb 2+ It has good adsorption effect. When pH≥3, its adsorption rate can reach more than 99%.
[0077] The nano-hydroxyapatite prepared in Example 1 of the present invention adsorbs Cd in water under different pH conditions. 2+ The removal rate effect was tested. Before adsorption, Cd 2+ is 100mg / l, the test results are as follows Fig.11 .Depend on Fig.11 It can be seen that under different pH conditions, the nano-hydroxyapatite prepared in Example 1 of the present invention has a significant effect on Cd 2+ It has good adsorption effect. When pH≥3, its adsorption rate can reach more than 98%.
[0078] The nano-hydroxyapatite prepared in Example 1 of the present invention adsorbs Zn in water under different pH conditions. 2+ The removal rate effect was tested. Before adsorption, Zn 2+ is 150mg / l, the test results are as follows Fig.11 .Depend on Fig.11 It can be seen that under different pH conditions, the nano-hydroxyapatite prepared in Example 1 of the present invention has a significant effect on Zn 2+ It has good adsorption effect. When pH≥4, its adsorption rate can reach more than 91%.
[0079] The nano-hydroxyapatite prepared in Example 1 of the present invention adsorbs Cu in water under different pH conditions. 2+ The removal rate effect was tested. Before adsorption, Cu 2+ is 200mg / l, the test results are as follows Fig.11 .Depend on Fig.12 It can be seen that under different pH conditions, the nano-hydroxyapatite prepared in Example 1 of the present invention has a significant effect on Cu 2+ It has good adsorption effect, and its adsorption rate can reach 93% at pH=6.
[0080] Nano-hydroxyapatite prepared in Example 1 of the present invention adsorbs Pb in water under different time conditions 2+ The removal rate of Pb in water before adsorption was tested. 2+ is 200mg / l, the test results are as follows Fig.12 .Depend on Fig.12 It can be seen that under different time conditions, the nano-hydroxyapatite prepared in Example 1 of the present invention has a significant effect on Pb 2+ It has good adsorption effect, and its adsorption rate can reach 99.52% in 10 minutes.
[0081] Nano-hydroxyapatite prepared in Example 1 of the present invention adsorbs Cd in water under different time conditions 2+ The removal rate of Cd in water before adsorption 2+ is 100mg / l, the test results are as follows Fig.12 .Depend on Fig.12 It can be seen that under different time conditions, the nano-hydroxyapatite prepared in Example 1 of the present invention has a significant effect on Cd 2+ It has good adsorption effect, and its adsorption rate can reach 98.10% at 720 minutes.
[0082] Nano-hydroxyapatite prepared in Example 1 of the present invention adsorbs Zn in water under different time conditions 2+ The removal rate of Zn in water before adsorption was tested. 2+ is 150mg / l, the test results are as follows Fig.12 .Depend on Fig.12 It can be seen that under different time conditions, the nano-hydroxyapatite prepared in Example 1 of the present invention has a significant effect on Zn 2+ It has good adsorption effect, and the removal rate is 90% at 700min.
[0083] Nano-hydroxyapatite prepared in Example 1 of the present invention adsorbs Cu in water under different time conditions 2+ The removal rate of Cu in water before adsorption was tested. 2+ is 200mg / l, the test results are as follows Fig.12 .Depend on Fig.12 It can be seen that under different time conditions, the nano-hydroxyapatite prepared in Example 1 of the present invention has a significant effect on Cu 2+ It has good adsorption effect, and the removal rate is 97.28% at 110min.
[0084] The nano-hydroxyapatite prepared in Example 1 was used to adsorb heavy metals of different concentrations according to the optimal dosage, optimal pH and optimal adsorption time to explore the maximum adsorption capacity of the nano-hydroxyapatite. The results are shown in Table 5. As can be seen from Table 5, the nano-hydroxyapatite prepared in Example 1 of the present invention adsorbs Pb in water under the optimal conditions. 2+ 、Cd 2+ , Cu 2+ 、Zn 2+ The maximum adsorption capacities are 1400 mg / g, 900 mg / g, 450 mg / g, and 538 mg / g, respectively.
[0085] Table 5 Maximum adsorption capacity of heavy metals by nano-hydroxyapatite prepared in Example 1
[0086]
[0087] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing potassium sulfate fertilizer and nano-hydroxyapatite using phosphogypsum, characterized in that: The following steps are involved: 1) dissolving phosphogypsum and potassium chloride in an ammonia-ethanol mixed solution to obtain slurry A; 2) centrifuging the slurry A to obtain a filtrate B and a filter residue; 3) evaporating and crystallizing the filtrate B to obtain calcium chloride; 4) washing the filter residue with water and then centrifuging to obtain filtrate C; 5) evaporating and crystallizing the filtrate C to obtain potassium sulfate; 6) After the calcium chloride is dissolved in water, phosphoric acid is added to adjust the solution pH to ≥ 10.5, and then, after stirring and reacting for a period of time, washing, centrifugal separation, and vacuum drying are performed to obtain nano-hydroxyapatite.
2. The method for preparing potassium sulfate fertilizer and nano-hydroxyapatite by using phosphogypsum according to claim 1, characterized in that: In step 1), the mass ratio of the phosphogypsum to the potassium chloride is 1:
1.
3. The method for preparing potassium sulfate fertilizer and nano-hydroxyapatite by using phosphogypsum according to claim 1, characterized in that: In step 1), the mass ratio of the total mass of the phosphogypsum and the potassium chloride to the ammonia-ethanol mixed solution is 1:10-1:
12.
4. The method for preparing potassium sulfate fertilizer and nano-hydroxyapatite by using phosphogypsum according to claim 1, characterized in that: The crystallization temperature of the evaporation crystallization in step 3) is 200° C. and the crystallization time is not less than 24 hours.
5. The method for preparing potassium sulfate fertilizer and nano-hydroxyapatite by using phosphogypsum according to claim 1, characterized in that: The crystallization temperature of the evaporative crystallization in step 5) is 200° C., and the crystallization time is not less than 18 hours.
6. The method for preparing potassium sulfate fertilizer and nano-hydroxyapatite by using phosphogypsum according to claim 1, characterized in that: The pH of the solution in step 6) is 10.5-11.
0.
7. The method for preparing potassium sulfate fertilizer and nano-hydroxyapatite by using phosphogypsum according to claim 1, characterized in that: The stirring rate of the stirring reaction in step 6) is ≥500 rpm, and the stirring time is ≥6 h.
8. The method for preparing potassium sulfate fertilizer and nano-hydroxyapatite by using phosphogypsum according to claim 1, characterized in that: The vacuum drying in step 6) is carried out at a drying temperature of 70° C. to 80° C. and for a drying time of 48 h.